Wild Europe : the Balkans in the gaze of Western travellers - Jezernik, Božidar (London : Saqi in association with the Bosnian Institute, 2004)
Combining witty commentary with meticulous research, and abounding in historical and cultural detail, Jezernik reveals how the Balkans have been perceived by Western European travellers and experts from the mid-sixteenth to the late twentieth century. Many of these travellers regarded the region as part of Asia, and sought accordingly to inform their contemporaries of its ‘exotic’, ‘outlandish’ and ‘primitive’ ways. The book’s rich store of source material includes citations from naturalists, geographers, historians and social scientists, including Joseph de Tournefort and Henry Blount via Karl Baedeker, William Gladstone, Paulina Irby, Edith Durham, Rebecca West and Julia Kristeva. Exploring over a thousand first-hand reports and comparing narratives spanning nearly 500 years, the author demonstrates that the act of observing other people in their environment mirrors the observer’s own culture and mentality. Thus the impressions passed down through the ages of the Balkans say more about Western Europe in most respects than about the lands and peoples in question
Bibliografija: str. [280]-311. - Kazalo
Keywords: Voyages and travels; Balkan Peninsula -- Civilization; Balkan Peninsula -- Social life and customs; Balkan Peninsula -- Description and travel; putovanja -- Balkanski poluotok - civilizacija -- Balkanski poluotok - društveni život i običaji